“I feel like it’s giving me a lot as a language teacher to be a learner myself”: Factors affecting the implementation of a multilingual pedagogy as reported by teachers of diverse languages - Calafato, Raees (Studies in Second Language Learning and Teaching, 2021)
To boost the foreign language learning process, language teachers need to know how to implement a multilingual pedagogy, that is, they should be able to draw on their and their students’ knowledge of other languages during lessons. This qualitative study explored the extent to which 21 foreign language teachers in Norwegian and Russian upper-secondary schools were willing and able to implement multilingual teaching practices and the factors that they thought affected this implementation. The findings revealed three main factors, namely, their language knowledge, their positioning as language learners, and the level of support they received, which the participants reported as strongly influencing the extent to which they were able and willing to draw on their and their students’ multilingualism as a pedagogical resource. The findings also indicated that participants did not implement multilingual teaching practices differently based on the languages they taught, although there were differences between the participants from Norway and Russia concerning the teaching of English. The study has important implications for research on language teaching and learning in multilingual environments, educational institutions, and teacher development programs.